More Depressive Symptoms, Alcohol and Drug Consumption: Increase in Mental Health Symptoms Among University Students After One Year of the COVID-19 Pandemic - Dogan-Sander, Ezgi; Kohls, Elisabeth; Baldofski, Sabrina; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2021)
As the majority of studies examining mental health during the pandemic are cross-sectional, little is known about the changes in mental health during the pandemic, especially in university students. Most studies indicate a worsening of mental health conditions. This study aimed to evaluate the mental health status of German university students during the third wave of the pandemic in 2021 and to compare the results to a sample of a congruent cross-sectional study from 2020. Two cross-sectional and anonymous online surveys among university students were conducted (first survey: July-August 2020, N = 3,382; second survey: March-April 2021, N = 5,642). Mental health status was assessed with standardized measures (depressive symptoms, alcohol and drug consumption, and eating disorder symptoms), and social and emotional aspects of the COVID-19 pandemic were assessed. In addition to descriptive statistics and group comparisons of the two survey samples from 2020 and 2021, respectively, risk and protective factors related to mental health were analyzed. There were significant differences in severities of depressive symptoms and alcohol and drug consumption between the two online surveys from 2020 and 2021. Findings suggest an increase in the severity of depressive symptoms as well as alcohol and drug consumption. Significantly more respondents reported suicidal ideation in the survey from 2021. Lower self-efficacy, less social support and lower resilience as well as higher perceived stress and more loneliness were reported by the participants of the survey from 2021 compared to 2020. Regarding factors predicting mental health symptoms, being female was a positive predictor for hazardous alcohol use and anorexia nervosa in comparison to men. Further, younger age, being diverse, higher perceived stress and loneliness were positive predictors for all mental health outcomes. This study reveals an increase in severities of depressive symptoms, including suicidal ideation, drug and alcohol consumption among students. Being diverse, younger age, higher perceived stress and loneliness were mutual risk factors for higher depressive and eating disorder symptoms as well as alcohol consumption. Universities and health care policy should recognize and address mental health issues of young adults during ongoing times of crisis and invest in easy-to-access interventions.